The relationship between retinal vessel geometrical changes to incidence and progression of Diabetic Macular Edema. (2019) - Ajaz, Aqsa; Kumar, Himeesh; Aliahmad, Behzad; Kumar, Dinesh K.
Abstract: Diabetic Macular Edema (DME) is the leading cause of vision loss in patients with diabetes. DME occurs when the damaged blood vessels inside the retina swell and leak leading to tissue swelling and vision distortion. Early detection and treatment of DME can decrease the risk of visual loss. This study has investigated the association between retinal vessel geometrical features (RVGF) to the severity of DME. A total of 352 color fundus images were analyzed: 143 normal, 67 grade 1 and 142 grade 2 from the MESSIDOR database. Retinal vessel geometrical features (RVGF) were automatically assessed using functions from the Retinal Image Vasculature Assessment Software (RIVAS). The results indicate that while the four RVGF showed a significant difference between controls and DME cases, Average Branching Angle (ABA) was the only parameter that showed a monotonic increase with the progression of disease. The study findings suggest that ABA of the retinal vessels can act as a potential biomarker indicative of progression of DME severity and suitable for computerized assessment of the DME.